The institutionalization and effectiveness of transnational policy transfer : the China–Singapore Suzhou Industrial Park as a case study - Liu, Hong (2021)
Transnational policy transfer through cross-border government-to-government collaboration projects has been widely adopted as a tool to facilitate economic growth, especially by developing countries. Why did some transnational projects of policy transfer succeed while others fail? What are the facilitating and constraining factors in shaping their fates? What are their theoretical and policy implications for public administration and economic development in a globalizing world? This article examines the case of the China–Singapore Suzhou Industrial Park which has been in operation since its establishment in 1994. Challenging the previous studies and adopting a mixed research method utilizing a wide range of quantitative and qualitative data, we identify three major factors affecting the results of policy transfer: (1) a systemic combination of “hardware” and “software” in the conceptualization of transnational policy transfer; (2) localization of transnational policy and its enforcement; and mostly importantly, (3) institutionalization of key processes in both ends of policy exchanges and implementation.